Figurative Language in The Song Lyrics of Laufey’s Album Bewitched - Natashya Haliza; I Gst. Ayu Gede Susiowati; Gek Wulan Novi Utami (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims at analysing the types of figurative language and explaining the types of meanings behind the figurative language found in the song lyrics of Laufey’s album titled “Bewitched”. The data was taken from thirteen songs in “Bewitched” album by Laufey. This study was conducted using qualitative method and the documentation method utilized by note-taking technique. This study employed the theory from Knickerbocker and Reninger (1965) to analyse the types of figurative language and the theory from Leech (1981) to analyse the types of meanings. The data analysis was presented in informal way. The results show that all types of figurative were found, with their use varying to illustrate different contexts in the album, from love, personal growth, and the complexities of life. The most dominant type of figurative language is metaphor. The analysis shows that these devices contribute to conceptual, connotative, social, affective, reflected, collocative, and thematic meanings in the lyrics. These different types of meaning allow the listener to develop a deeper connection and understanding of the music. This study contributes to a comprehensive understanding of the diverse use of figurative language across various literary works.